Iowa Ornithologists' Union, Quarterly field report, fall 1977 - Halmi, Nicholas S.et al; Iowa Ornithologists' Unionet al (1977)
Quarterly field report for the fall of 1977 titled "Field reports fall 1977." Epson - sheet feed